Mitochondrial pathways in sarcopenia of aging and disuse muscle atrophy - Calvani, Riccardo; Joseph, Anna-Maria; Adhihetty, Peter J; Miccheli, Alfredo; Bossola, Maurizio; Leeuwenburgh, Christiaan; Bernabei, Roberto; Marzetti, Emanuele (Biological chemistry, 2013)
Muscle loss during aging and disuse is a highly prevalent and disabling condition, but knowledge about cellular pathways mediating muscle atrophy is still limited. Given the postmitotic nature of skeletal myocytes, the maintenance of cellular homeostasis relies on the efficiency of cellular quality control mechanisms. In this scenario, alterations in mitochondrial function are considered a major factor underlying sarcopenia and muscle atrophy. Damaged mitochondria are not only less bioenergetically efficient, but also generate increased amounts of reactive oxygen species, interfere with cellular quality control mechanisms, and display a greater propensity to trigger apoptosis. Thus, mitochondria stand at the crossroad of signaling pathways that regulate skeletal myocyte function and viability. Studies on these pathways have sometimes provided unexpected and counterintuitive results, which suggests that they are organized into a complex, heterarchical network that is currently insufficiently understood. Untangling the complexity of such a network will likely provide clinicians with novel and highly effective therapeutics to counter the muscle loss associated with aging and disuse. In this review, we summarize the current knowledge on the mechanisms whereby mitochondrial dysfunction intervenes in the pathogenesis of sarcopenia and disuse atrophy, and highlight the prospect of targeting specific processes to treat these conditions.